2019
DOI: 10.1021/acs.est.8b05587
|View full text |Cite
|
Sign up to set email alerts
|

Osmotically and Thermally Isolated Forward Osmosis–Membrane Distillation (FO–MD) Integrated Module

Abstract: In this study, we propose a novel module design to integrate forward osmosis (FO) and membrane distillation (MD). The two processes are sealed in one module and operated simultaneously, making the system compact and suitable for a wide range of applications. To evaluate the system under large-scale module operating conditions, FO and MD experiments were performed separately. The effect of draw solution (DS) temperature on the FO performance was first assessed in terms of flux, reverse salt flux (RSF), and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 57 publications
(136 reference statements)
3
21
0
Order By: Relevance
“…It shows that the FO flux increased from 11.17 ± 3.85 to 30.19 ± 5.51 L m −2 h −1 when the temperature differences was increased from 20 to 60 °C, which was comparable with other studies [ 36 , 39 , 40 , 41 ]. As reported by Kim et al [ 36 ], the significant augmentation of water flux could be justified by analyzing two effects: ( i ) an increase in osmotic pressure induced by high temperature, according to the van ’t Hoff equation [ 42 ] and ( ii ) an increase in the diffusivity of draw solutes due to an increase of DS temperature according to Stokes–Einstein equation which reduced the mass transfer resistance [ 43 ]. Increasing the temperature of DS promoted the heat transfer to the FS across the FO membrane due to temperature polarization.…”
Section: Resultssupporting
confidence: 91%
“…It shows that the FO flux increased from 11.17 ± 3.85 to 30.19 ± 5.51 L m −2 h −1 when the temperature differences was increased from 20 to 60 °C, which was comparable with other studies [ 36 , 39 , 40 , 41 ]. As reported by Kim et al [ 36 ], the significant augmentation of water flux could be justified by analyzing two effects: ( i ) an increase in osmotic pressure induced by high temperature, according to the van ’t Hoff equation [ 42 ] and ( ii ) an increase in the diffusivity of draw solutes due to an increase of DS temperature according to Stokes–Einstein equation which reduced the mass transfer resistance [ 43 ]. Increasing the temperature of DS promoted the heat transfer to the FS across the FO membrane due to temperature polarization.…”
Section: Resultssupporting
confidence: 91%
“…This hypothesis was previously presented by Goosen et al [46] whose work revealed a change in the membrane's pore size when the feed solution temperature increases from 30 °C to 40 °C. Other studies also found an optimum Jw and RSF under different draw solution temperatures [47]. In our study, we also find that the temperature near the membrane surface affects more the Jw and RSF than the bulk temperatures (Fig.…”
Section: Influence Of Draw and Feed Temperaturessupporting
confidence: 84%
“…Each of these processes has advantages at the cost of more or less severe drawbacks and their association with MD offers improvement opportunities. Kim et al [129] proposed a novel module design to integrate FO and MD. The two processes are sealed in one module and operated simultaneously, making the system compact and suitable for a wide range of applications.…”
Section: Hybrid and Integrated Systemsmentioning
confidence: 99%